Evaluation of Risk Factors and Clinicopathologic Features for Intrahepatic Cholangiocarcinoma in Southern China: A Possible Role of Hepatitis B Virus - Peng, Ning-fu; Li, Le-qun; Qin, Xiao; Guo, Ya; Peng, Tao; Xiao, Kai-yin; Chen, Xi-gang; Yang, Yu-feng; Su, Zhi-xiong; Chen, Bin; Su, Ming; Qi, Lu-nan (Annals of surgical oncology, 2011)
Background Recent efforts suggest an etiologic role of hepatitis B virus (HBV) infection in intrahepatic cholangiocarcinoma (ICC) and the involvement of hepatic progenitor cell in ICC development, without definitive conclusions. This case-control study was undertaken to investigate risk factors for ICC, and clinicopathological features of HBV-associated ICC were analyzed. Methods The report comprised 98 patients with pathologically confirmed ICC and 196 healthy control subjects. Logistic regression was used to determine odds ratios and 95% confidence intervals. The sex and age distributions of HBV-related and unrelated ICC patients were compared respectively with those of 882 HBV-associated hepatocellular carcinoma patients from a random selection, and the clinicopathological data of 62 ICC patients with or without HBV infection undergoing surgical resection were compared. Results There was an association between ICC and each of HBV infection, liver cirrhosis, hepatolithiasis, and liver fluke infestation with the odds ratios (95% confidence intervals) of 2.75 (1.27–5.95), 8.42 (2.50–28.37), 22.81 (7.16–72.68), and 3.55 (1.60–7.89), respectively, with a marked synergism of cirrhosis and HBV infection (20.67; 5.40–79.06). Compared with HBV-unrelated ICC patients, HBV-related ICC patients were more common in male and younger subjects, had a higher incidence of abnormal serum alfa-fetoprotein level, cirrhosis, and neutrophilic infiltration, and had a lower proportion of elevated carbohydrate antigen 19-9 (CA19-9) values. Conclusions The independent association of HBV infection with ICC, synergy between cirrhosis and HBV infection, and some clinicopathological similarities between HBV-related ICC and hepatocellular carcinoma suggests that both may share similar or common tumorigenic process and may possibly originate from malignant transformation of hepatic progenitor cell.